Analysis of Leadership Style and Work Motivation of Vocational School Principals on School Sports Achievement in Merangin District, Jambi Province - Hendra, Toni; nugraha, Ugi; saputra, Endarman; sukendro, Sukendro; ali, Muhammad; indrayana, Boy (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
ABSTRACT: Education is one aspect that is very important and necessary for the country to be able to compete with the outside world. The quality of education in Indonesia really needs to be improved because high quality education indicates that a nation has potential and quality human resources. Education is also inseparable from the role of an educator, school principal or leader who is professional and dignified. The role of an educator or teacher cannot be separated from providing knowledge, guiding, directing, training students so that they have the knowledge to be able to face their future life in accordance with the changes and developments of the times. A quality leader will direct the success of the vision and mission that has been designed. Therefore, to achieve the expected vision and mission, a leadership style that is Democratic, Visionary, Multicultural, Sportive, Transactional, Transformational and Liberal Leadership is needed. This research aims to analyze the leadership style of school principals, assess the various leadership styles applied by vocational school principals in Merangin Regency and identify their influence on the development of sports achievements in schools. In this research the author used qualitative methods with data collection techniques through interviews, observation and documentation. What is the leadership style applied by vocational school principals throughout Merangin Regency in terms of sports achievements in their schools?